(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
Technological advances not only lie in the speed factor to get information but also multimedia facilities that can make learning more interesting to encourage students to learn optimally both in independent learning and in classroom learning. This study aims to determine the level of learning quality of UPN "Veteran" Jakarta 5th semester medical students on the use of the LeADS application. The type of research used is quantitative research with experimental methods. Research data were obtained using instruments (questionnaires) based on population and sample using quantitative data analysis to test hypotheses. Data collection techniques in this study were carried out by distributing questionnaires in the form of google forms containing checklists. The results of the analysis show that the use of the LeADS application to improve the quality of medical student learning is still not good when compared to the expectations of medical students in the future in improving the quality of learning. Recommendations for future research are that it is necessary to improve indicators that have not run well / effectively and find solutions to various obstacles in online learning, so that the quality of online learning increases